2001
DOI: 10.1590/s1519-566x2001000400032
|View full text |Cite
|
Sign up to set email alerts
|

Fauna de Homoptera: Auchenorrhyncha em Pomares de Ameixeira em Santa Catarina

Abstract: -The Homoptera: Auchenorrhyncha fauna of plum orchards in an area of epidemic spread of plum leaf scald disease in mid-west Santa Catarina State, Brazil were surveyed in 1991 and 1992 to search for plum leaf scald vectors. The homopterans were sampled by sweeping net and yellow water pan traps and when possible submitted to ELISA assay to detect Xylella fastidiosa bacteria. A total of 112 species were caught, distributed in the families Aethalionidae (1 species), Cercopidae (7), Cicadellidae (64), Cixiidae (3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
13

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 9 publications
0
6
0
13
Order By: Relevance
“…However, in studies surveying entomofauna they are always present (Yamamoto & Gravena, 2000;Hickel et al, 2001;Favretto et al, 2013). Colonial species are less active and easy to collect, their life cycles are closely related to the host plant, and they have a stable classification.…”
mentioning
confidence: 99%
“…However, in studies surveying entomofauna they are always present (Yamamoto & Gravena, 2000;Hickel et al, 2001;Favretto et al, 2013). Colonial species are less active and easy to collect, their life cycles are closely related to the host plant, and they have a stable classification.…”
mentioning
confidence: 99%
“…No Brasil, há grande diversidade de cigarrinhas em pomares de citros (Yamamoto & Gravena 2000, Ott et al 2006, Miranda et al 2009, de ameixa (Hickel et al 2001) e em cafezais (Giustolin et al 2009), sendo que várias espécies de Cicadellinae já foram descritas como vetoras de X. fastidiosa em citros e cafeeiro (Roberto et al 1996, Yamamoto et al 2002, 2007, Marucci et al 2008. Entretanto, ainda não existem informações a respeito de espécies de cigarrinhas em videira que poderiam atuar como vetoras de X. fastidiosa.…”
unclassified
“…Various studies in southern and southeastern Brazil have revealed a large diversity of sharpshooter species occurring in orchards of plum (Hickel et al 2001;Lopes et al 2008), citrus (Yamamoto & Gravena 2000;Ott et al 2006), coffee (Giustolin et al 2009), and grape (Ringenberg et al 2010), and many of these species have already been identified as vectors of X. fastidiosa in citrus and coffee (Roberto et al 1996;Krügner et al 2000;Yamamoto et al 2002;Marucci et al 2008). However, there is no information on leafhopper or spittlebug species occurring in grapevine orchards in the region of the São Francisco River Valley, in northeastern Brazil, that could act as vectors of X. fastidiosa.…”
mentioning
confidence: 99%